Homoseksual menurut Thanthawi Jauhari dalam Kitab al-Jawahir fi Tafsir Al-Qur`an al-Karim - Febriani, Nurul Delfira; Bustamam, Risman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The aim of this research is to find out the interpretation of verses about homosexuality in the Al-Qur'an according to Thanthawi Jauhari as a mufassir 'ilmi and how relevant Thanthawi Jauhari's thoughts are regarding the current homosexual phenomenon. The type of research used is library research. The analytical method used is the thematic interpretation method using the keyword الفَاحِشَة. Meanwhile, to analyze the interpretation of homosexual verses by Thanthawi Jauhari, the character-based maudu'i interpretation method was used, through content analysis, interpretive science approaches, and hermeneutics. The results of this research conclude that as a mufassir 'ilmi, Thanthawi Jauhari interprets verses about homosexuals using a scientific approach with the following details: 1) Thanthawi Jauhari in his book interprets the meaning of the word الفَاحِشَة contained in the QS. al-A'raf [7]: 80, QS. an-Naml [27]: 54, QS. al-'Ankabut [29]: 28 textually means a heinous act and contextually (the meaning of the verse QS. al-A'raf [7]: 81, QS. an-Naml [27]: 55, QS. al-' Ankabut [29]: 29) means homosexual. He explained that the Sodomites had ignored the wisdom of creating humans in pairs and cut off the path of descent by committing sexual deviations in the form of having sex with the same sex which resulted in the fertilization process not occurring. 2) Thanthawi Jauhari's scientific thinking is very relevant to the current homosexual phenomenon. According to science, if a sperm cell meets an egg cell, fertilization will occur. Psychologically, sexual deviant behavior will result in the perpetrator experiencing a decrease in their ability to think.